Pengaruh Tingkat Kesadaran Halal Suplai Chain Dalam Mendorong Keputusan Pembelian (Halal Food UMKM MEDAN) - Mutia Sari; Shelvi Fadillah Harahap; Siti Aisyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Indonesia is currently a developing country seeking to improve its economic sector in all areas, including the industrial sector. The enactment of the Halal Product Warranty Act (UUJPH) guarantees the convenience, safety and availability of Halal products in the consumption and use of Halal products and in the consumption and use of products by the general public. idea. The purpose of this survey is to provide information on the impact of SMEs in Medan's perception of the Halal supply chain on halal food purchase decisions. The sample for this survey is a consumer of Medan SMEs with a total of 40 respondents. This survey or survey uses a quantitative method by collecting data through voting shared on social media such as WhatsApp and Instagram. The data processing used in this study is to use SPSS version 25 for validation, reliability, correlation, and hypothesis testing. The results of this survey show that awareness of the Halal supply chain has a significant impact on Medan SMEs' purchasing decisions.